What makes a leader? - Goleman, Daniel (Harvard Business Review Press, 2017)
The Harvard Business Review Classics series offers you the opportunity to make seminal Harvard Business Review articles a part of your permanent management library. Each highly readable volume contains a groundbreaking idea that continues to shape best practices and inspire countless managers around the world―and will have a direct impact on you today and for years to come.